THE EFFECTS OF THE ENVIRONMENTAL FACTORS ON THE PERFORMANCE OF THE RENDERINGS: A REVIEW - Yatagan, Mehmet Serkan (IJRDO - Journal of Mechanical And Civil Engineering, 2019)
The renderings are the last coatings of the buildings and the renderings face the environmental effects directly thus they are more effected by the environmental factors than the other components. The performance requirements of the renderings are determined by the environmental factors. The main goal is to set and fulfil these requirements for the best performance of the renderings.These environmental factors are U.V, the moisture, thermal conditions, CO2, SO2 or SO3, Cl ions, acids and the salts. These environmental factors have peculiar degradation mechanisms but at last the degradations of the renderings are the same such as cracking, disintegrating, shrinking or corrosion.As examples of the degradation mechanisms of the environmental factors; U.V breaks the bonds between the polymers of the polymer based renderings and the renderings spoil. CO2 penetrates through the renderings and form carbonation so the volume changes and the renderings disintegrate. As a result of Sulphur affect, the corrosion occurs then the renderings cannot supply the requirements. The penetration of the driving rain through the renderings is hazardous if the evaporation of the water is not sufficient. The moisture harms the structure of the renderings by forming damp, mould growth and spoiling the adhesion between the substrate and the renderings and the structure of the renderings by the freeze-thaw. Due to the thermal changes, the renderings shrink or expand. If these events repeat, the renderings spoil.Besides, the acidic or base character of the renderings form degradation mechanisms, as well. On the other hand, the salt ratios of the renderings should be considered, too since high salt ratios form crystallization in the renderings then this crystallization compress surround and the renderings disintegrate. Shortly, investigating the performance of the renderings is the most important topic because the effects of the environmental factors form different degradation mechanisms and the renderings spoil so the renderings are not capable of supplying the performance requirements. When the performance of the renderings decrease, degradation mechanisms continue to harm the substrate. Consequently, the performance of the building will be lost. This work helps knowing the environmental factors and their degradation mechanisms so that we can take precautions. The performance of the renderings means to answer the requirements. Understanding the environmental factors and their degradation mechanisms, it is possible to get the renderings which supply the required functions.